Pengaruh Ketebalan Orifis Terhadap Karakteristik Hidrodinamik Oksigen Terlarut pada Microbubble Generator Tipe Porous-Orifis - Agus Santoso; Radhi Ariawan; Bayu Aji Girawan; Ghia Pisti Cikarge (Infotekmesin, 2026)
This study aims to analyze the effect of orifice thickness on the performance of a porous-orifice microbubble generator (MBG) in aeration processes, particularly concerning the enhancement of dissolved oxygen (DO) concentration and the volumetric oxygen mass transfer coefficient (KLa). The primary issue identified is the limited number of studies that explicitly address the role of orifice thickness as a critical geometric parameter influencing microbubble formation and oxygen transfer efficiency. The research was conducted experimentally under controlled laboratory conditions using two orifice thickness variations, 1.5 mm and 9 mm, with different water and air flow rates, QL and QG. The findings reveal that increasing air flow rate (QG)  correlates positively with higher KLa values for both orifice types; however, the thinner orifice consistently demonstrates superior KLa performance. This behavior is attributed to a steeper pressure gradient and stronger shear forces that promote finer bubble fragmentation and greater gas–liquid interfacial area. Overall, the thin-orifice MBG proved more efficient in enhancing aeration performance compared to the thick-orifice configuration.